The Roles of Brand Attributes towards Green Purchase Intention - Immawan, Taufiq; Ridwan Andi Purnomo, Muhammad; Indrawati, Sri; Nur Hana Kurnia, Desi (International Journal of Psychosocial Rehabilitation, 2020)
The quantitative research is aimed at investigating the relationship between non-product-related attributes of green marketing and green purchase intention in one of the best-known coffee shops in the world. Green marketing has become a trend in every country. The trend of shifting consumer’s consumption patterns from consuming conventional to organic products has become an interesting phenomenon today. The concern of consumers with green marketing has increased since the rising level of consumer awareness towards green products. In this research, there are three independent variables and one dependent variable involved. The independent variables come from non-product-related attributes, which are green price, green packaging, and user imagery, while the dependent variable is green purchase intention. By spreading online questionnaires, the data is collected from 155 respondents aged above 18 years old in Yogyakarta who have known or visited the company. The analysis is performed through the Structural Equation Model (SEM) method with IBM AMOS 22 and SPSS software. The findings confirmed that green price and green packaging significantly influence the green purchase intention. The result shows that green price has the highest influence on green purchase intention, followed by green packaging.